(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This paper examines the cooperation between Kyrgyzstan and China, assessing its current state and development prospects. The main aspects of economic and cultural interaction between the two countries are analyzed.